Comparative Study of Parents' Satisfaction Rate toward Baiturrahmah Daycare Service - R. Siti Aisah; Lince Sari Dianawati Leatemia (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2019)
This research aims to investigate satisfaction change rate of parents before and after they drop their children at Baiturrahmah Daycare. Implementing the quantitative approach, data is gathered through questionnaire and literary studies. Research hypotheses are tested through the Wilcoxon method by comparing two paired samples. With 5% test rate, the results show that there are no significant parents satisfaction rate increase before and after they drop their children. Furthermore, according to the samples’ opinions, their expectations of the service quality before they drop their children met what service they are provided by the daycare—this discouraged the satisfaction rate increase.